Factors Affecting the Adoption of Modern Agricultural Techniques on Wheat Cropping in Hama Province /Syria - سفاف جعفر; حيان سليمان (Latakia University Journal -Biological Sciences Series, 2024)
This research has been conducted on Hama province, depending on elementary data of wheat farmers’ sample, sized to 150 farmers, which were collected randomly during the wheat growing season at 2022-2023, in purpose to define the main factors that determine using of modern technologies in wheat production in Syria. The results have shown high dominance of surface irrigation on wheat cropping compared to (27.5 %) only for spray method. the tow variables of soil fertility and the availability of groundwater wells, have formed key factors influencing the adoption of this technique, means providing fertile soil will raise the probability of adopting it by 12.6% increasing compared with moderate fertility land and (25.3%) compared with poor one .The availability of groundwater wells will increase this adoption by (19.3 % ) compared with the case of non - availability of irrigation wells. Significantly, the adoption of organic fertilizers technique was affected by the degree of soil fertility, which are more likely to be adopted by an increasing estimated to (23%) when moving from medium- fertility land to the poor, or from fertile land to moderate fertility. The results have also shown low of most farmers on each of crop rotation and recommended seed rate by the local research institutions, where about (77.4 %) of the sample farmers have sowed greater amounts of wheat seeds by (30%). For other important technique “the wheat cultivars” it has been found that they mostly based on modern cultivars with cropping ratio (97.8%).